TRANSIENT EXPRESSION OF HUMAN G-CSF IN NICOTIANA BENTHAMIANA PLANTS USING A TOMATO BUSHY STUNT VIRUS – BASED VECTOR - Abeuova , L.S.; Scholthof , H.B.; Ramankulov , E.M.; Manabayeva , S.A. (Eurasian Journal of Applied Biotechnology, 2015)
Plants have been proposed as an attractive alternative to mammalian or microbial cell-based systems for pharmaceutical protein production. Foreign proteins can be produced in plants by stable transformation or by transient expression using virus-based vectors. Several plant virus vectors have been developed for transient expression of fоreign proteins, including tobacco mosaic virus (TMV), potato virus X (PVX) and tobacco rattle virus (TRV). The objective of this work was to develop an advanced Tomato bushy stunt virus (TBSV) – based protein production system to produce human G-CSF in non-transgenic plants. A significant advantage of the TBSV vector system is that the TBSV genome encodes the p19 protein, which is capable of inhibiting posttranscriptional silencing and enhancing expression levels for each gene in the viral RNA (including heterologous ones). We evaluated the potential of the TBSV vector system for efficient expression of the recombinant human G-CSF (rhG-CSF) protein in Nicotiana benthamiana plants. For this purpose, we developed a TBSV derived viral vector driven by the CaMV 35S promoter that can be delivered as DNA. In this vector, the CP gene was replaced by the codon optimized G-CSF (174 a.a., molecular weight 18.6 kDa) gene, which was synthesized by a PCR-based gene synthesis method. The viral vector was delivered into 4-5 week old N.benthamiana plants by agroinfiltration. Four days after infiltration, expression of rhG-CSF was verified by protein extraction followed by western blot procedures. The preliminary results indicate that the TBSV - based protein production system is suitable for transient production of biopharmaceuticals in plants.